2021
DOI: 10.1155/2021/4504030
|View full text |Cite
|
Sign up to set email alerts
|

Family Cohesion Is Associated with the Self-Perceived Need for Dental Treatment among Adolescents

Abstract: This study explored the association between family cohesion and self-perceived need for dental treatment among adolescents. A school-based representative cross-sectional study was conducted with 746 students aged 15 to 19 randomly selected from schools in Campina Grande, Brazil. Parents/guardians provided information on sociodemographic data, and students completed questionnaires about the self-perceived need for dental treatment, dental pain, and family cohesion and adaptability (FACES III). Two dentists were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Symptomatic and functional parameters, such as toothache and the loss of the first permanent molars, also exerted an influence on the self-perceived treatment need, a result similar to that found in other studies [1,5]. This finding demonstrates that adolescents are more affected when the condition is more evident, affecting both esthetics and function.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Symptomatic and functional parameters, such as toothache and the loss of the first permanent molars, also exerted an influence on the self-perceived treatment need, a result similar to that found in other studies [1,5]. This finding demonstrates that adolescents are more affected when the condition is more evident, affecting both esthetics and function.…”
Section: Discussionsupporting
confidence: 84%
“…In the adjusted analysis, active caries on anterior teeth were not associated with the self-perceived treatment need. On the other hand, previous studies analyzing clinical factors found an association between tooth decay in the anterior and posterior teeth and the self-perceived treatment need in adolescents in the same age group [1,5]. The prevalence of active caries on anterior teeth was 57.7%, and the mean number of caries on anterior teeth was low 1.62 (2.04).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations